The panarion of Epiphanius of Salamis. - Epiphanius, Saint, Bishop of Constantia in Cyprus, ca. 310-403. (Nag Hammadi and Manichaean Studies, 2009)
Epiphanius, monastic founder and bishop of Salamis on Cyprus for almost 40 years of the fourth century, threw heart and soul into the controversies of the time and produced the \'Panarion\' or \'Medicine Chest\', an historical encyclopedia of sects and heresies and their refutations. Book I, concerned chiefly with Gnostic and Jewish Christian groups, deals with material which is also found in Nag Hammadi and other Gnostic writings and in such patristic authors as Irenaeus, Hippolytus et al, and reproduces documents not available elsewhere. Its translation has been found useful by students of Nag Hammadi and Gnosticism, patrologists, historians of religion, church historians, students of Judaism, and the theologically minded public.